Information technology project management - Schwalbe, Kathy (Thomson/Course Technology, 2004)
Every recent innovation in IT can be traced back to a project. This title builds an unparalleled foundation for tomorrow's creators and managers by providing meaningful examples of real projects - both successful and failed - and applying the lessons to a sound framework in IT project management